A strategy for IMF reform - Truman, Edwin M. (Washington. D.C. : Institute for international economics, u.s., 2006)
The International Monetary Fund (IMF) is in eclipse as the preeminent institution promoting international economic and financial stability. This book argues that systemically important countries, starting with the Group of Seven, must support the IMF.
1. The Agenda for IMF Reform; 2. Introduction; 3. IMF's Role in the International Monetary System; 4. Governance; 5. Lending Facilities; 6. Financial Resources.
Keywords: IMF; IMF; International finance